(untitled) (Zoological Records and Reviews, 2025)
Invasive alien animal species (IAAS) are the second leading cause of global biodiversity loss after habitat destruction, yet their conservation implications vary enormously with invasive species identity, invaded ecosystem type, and the vulnerability of native assemblages. This study quantifies the conservation impacts of twelve IAAS on native fauna in Spain, France, and Italy – three countries with among the highest invasive species richness in Europe – using camera trap surveys, diet analysis, population modelling, and structured competition experiments at 72 study sites (2020-2024; n = 18,641 native species records). Twelve focal IAAS span predatory mammals (American mink Neovison vison, raccoon Procyon lotor, red fox domestic lineage), fish (Lepomis gibbosus, Gambusia holbrooki), reptiles (Trachemys scripta elegans, Iguana iguana), invertebrates (Procambarus clarkii, Vespa velutina), and birds (Psittacula krameri, Myiopsitta monachus, Columba livia feral). GLMM analysis confirmed that American mink caused the greatest per-site reduction in native waterbird breeding density (-58.4 +- 7.8%; z = -7.48, p < 0.001) and amphibian community richness (-42.4 +- 6.8%) of any focal IAAS. Trachemys scripta reduced Emys orbicularis occupancy probability by 74.8% at invaded sites. Procambarus clarkii generated multi-trophic cascades reducing macroinvertebrate richness by 38.4% and waterbird foraging success by 28.4%. Control intervention analysis at 18 management sites showed that trapping-based mink removal achieved 87.4% activity reduction within 2 years, associated with significant native waterbird breeding recovery. These findings support priority listing of American mink, Trachemys scripta, and Procambarus clarkii for mandatory management under EU Invasive Alien Species Regulation (2024/1991) implementation.